VvmiR160s/VvARFs interaction and their spatio-temporal expression/cleavage products during GA-induced grape parthenocarpy - Wenying Zhang; Mostafa Abdelrahman; Songtao Jiu; Le Guan; Jian Han; Ting Zheng; Haifeng Jia; Changnian Song; Jinggui Fang; Chen Wang (BMC Plant Biology, 2019)
Abstract Background Grape (Vitis vinifera) is highly sensitive to gibberellin (GA), which effectively induce grape parthenocarpy. Studies showed that miR160s and their target AUXIN RESPONSIVE FACTOR (ARF) responding hormones are indispensable for various aspects of plant growth and development, but their functions in GA-induced grape parthenocarpy remain elusive. Results In this study, the morphological changes during flower development in response to GA treatments were examined in the ‘Rosario Bianco’ cultivar. The precise sequences of VvmiR160a/b/c/d/e and their VvARF10/16/17 target genes were cloned, sequenced and characterized. The phylogenetic relationship and intron-exon structure of VvARFs and other ARF family members derived from different species were investigated. All VvmiR160s (except VvmiR160b) and VvARF10/16/17 had the common cis-elements responsive to GA, which support their function in GA-mediated grape parthenocarpy. The cleavage role of VvmiR160s-mediated VvARF10/16/17 was verified in grape flowers. Moreover, spatio-temporal expression analysis demonstrated that among VvmiR160 family, VvmiR160a/b/c highly expressed at late stage of flower/berry development, while VvARF10/16/17showed a reverse expression trend. Interestingly, GA exhibited a long-term effect through inducing the expression of VvmiR160a/b/c/e to increase their cleavage product accumulations from 5 to 9 days after treatment, but GA enhanced the expressions of VvARF10/16/17 only at short term. Pearson correlation analysis based on expression data revealed a negative correlation between VvmiR160a/b/c and VvARF10/16/17 in flowers not berries during GA-induced grape parthenocarpy. Conclusions This work demonstrated that the negative regulation of VvARF10/16/17 expression by VvmiR160a/b/c as key regulatory factors is critical for GA-mediated grape parthenocarpy, and provide significant implications for molecular breeding of high-quality seedless berry.